Skin tags as a symptom of metabolic disorders - Agnieszka Owczarczyk-Saczonek; Waldemar Placek (Termedia Publishing House, 2016)
Skin tags are classified as benign lesions. They occur mainly on the skin of the neck, eyelids, armpits, and groin as pedicles and soft nodules. Their occurrence is associated with obesity, insulin resistance, atherogenic lipidemia, and metabolic syndrome, as well as increased risk of atherosclerosis. In the pathogenesis factors which are impaired in obesity, such as leptin, insulin resistance associated with obesity (IGF-1), androgens and estrogens believed to stimulate the receptors on keratinocytes and fibroblasts to grow, may play a role. In addition, these receptors are stimulated by tryptase released from the mast cells by mechanical injuries. Probably HPV plays a role as a cofactor. The dermatological literature does not provide much information about this subject, so the authors draw attention to the link between the presence of skin tags and the development of metabolic disorders.